Performance of firebrick resistance-heated energy storage for industrial heat applications and round-trip electricity storage. (15th May 2019) - Stack, Daniel C.; Curtis, Daniel; Forsberg, Charles
Highlights: FIRES thermal energy storage is proposed as an affordable path to decarbonization. Charge, discharge and heat leakage simulations are presented over the design space. FIRES costs are estimated and discussed with respect to performance tradeoffs. Flexible cycling and storage duration can accommodate intermittent electricity. Electricity market case study shows short payback period and reduced emissions. Abstract: In the absence of an affordable and deployable energy storage option, the intermittency of renewable energy creates mismatches in supply and demand that limit the viability of a low-carbon electricity grid. High temperature electrically-heated thermal energy storage (E-TES) is a largely unexplored approach to alleviating the problem of low-value renewable energy. Evaluated herein is one E-TES concept, called Firebrick Resistance-Heated Energy Storage (FIRES), that stores electricity as sensible high-temperature heat (1000–1700 °C) in ceramic firebrick, and discharges it as a hot airstream to either (1) heat industrial plants in place of fossil fuels, or (2) regenerate electricity in a power plant. FIRES storage media and heater options are reviewed, and discharge cycling is simulated with Crank-Nicolson finite difference schemes and evaluated over the parameter design space. We report that systems of 100–1000 s MWh may be cycled daily, and discharged at a constant heat rate typically for 70–90% of the storage capacity. Traditional insulation can reasonably limit heat leakage to less than 3% per day. Preliminary cost estimates indicate a system cost near $10/kWh, substantially less expensive than batteries. Northwestern Iowa market analysis shows payback within 2 years and economic profitability.